Accountability and Legal Protection Against Notaries for Legally Defective Deeds (Study of Decision Number 65/Pdt.G/2020/PN Kdi) - Mentari Utami, Amelia; Rodhiyah Dwi Istinah, Siti (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study discusses the responsibilities and legal protection of notaries as public officials against defective deeds according to the Notary Law (UUJN). Notaries have a strategic role as public officials who are authorized by the state to make authentic deeds that have perfect evidentiary power. However, in practice it is not uncommon to find deeds that are defective both formally and materially, resulting in legal consequences, both for the parties and for the notary himself. The purpose of this study is to analyze the form of notary responsibility for defective deeds and the form of legal protection provided to notaries according to the provisions of the UUJN. This study employs a normative juridical legal research method with a statute approach and a conceptual approach. This study employs the Theory of Legal Certainty, the Theory of Legal Responsibility, and the Theory of Legal Protection as analytical tools. Data were obtained from primary legal materials in the form of laws and regulations and secondary legal materials in the form of literature, books, and legal journals. The research results show that a notary's liability for legally flawed deeds can take the form of civil and administrative liability, depending on the level of error and the consequences. On the other hand, legal protection for notaries is regulated in the UUJN, specifically through the Notary Honorary Council (MKN) mechanism as stipulated in Article 66 of the UUJN, which functions as a form of preventive and repressive protection for notaries in carrying out their duties. A balance between responsibility and legal protection is necessary to ensure legal certainty and maintain the integrity of the notary profession in Indonesia.